(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
This article delves into the foreign experience concerning information cooperation among organizations in procurement activities. Through a meticulous examination of existing literature and methodologies, it explores various approaches, results, and implications. By synthesizing findings, it offers insights into enhancing information exchange strategies in procurement, facilitating efficient and transparent processes globally.